Therapeutic outcome of saroglitazar, a peroxisome proliferator activated receptor α/γ agonist in diabetic and non-diabetic metabolic dysfunction associated steatotic liver disease - Shah, Nisar A.; Paul, Shashi; Parveen, Shagufta; Bhat, Mohammad Hayat; Ali, Irfan; Kadla, Showkat A. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Metabolic dysfunction associated steatotic liver disease (MASLD) is the most common cause of chronic liver disease (CLD)and its consequences throughout the world, more so in developed countries. It is more concerning in view of the lack of a definitive treatment. Aside from lifestyle changes and vitamin E, we are still looking for a drug that can improve outcome in this group of patients. Methods: Authors evaluated the safety and effectiveness of saroglitazar in MASLD/MASH patients in this 48-week prospective observational study, with the primary goal of evaluating the therapeutic outcome of saroglitazar on the NAFLD fibrosis score (NFS) in both diabetics and non-diabetics. After receiving written informed consent from each patient, a total of 292 patients who met the inclusion criteria were enrolled. However, only 257 individuals completed the study. Eligible patients were put on saroglitazar 4 mg per day for 24 weeks and followed on an OPD basis for 48 weeks with special emphasis on NFS, BMI, HbA1c, lipid levels, and liver biochemistry. Authors observed a male dominance (61.9%), a significant improvement in lipid profile, liver biochemistry, HbA1c, NFS, and liver stiffness measurement (LSM), and also an improvement in BMI though not statistically significant. Authors did not observe any significant drug related adverse events during the treatment with saroglitazar. Conclusion: In our study, saroglitazar at a dose of 4 mg per day for 24 weeks resulted in marked improvements in liver biochemistry, lipid profile, HbA1c, NFS, and LSM, in patients of MASLD/MASH in both diabetics and non-diabetics.